An electrospun lignin/polyacrylonitrile nonwoven composite separator with high porosity and thermal stability for lithium-ion batteries. Issue 122 (24th November 2015) - Zhao, Man; Wang, Jing; Chong, Chuanbin; Yu, Xuewen; Wang, Lili; Shi, Zhiqiang
Abstract : In this work, lignin/polyacrylonitrile composite fiber-based nonwoven membranes (L–PANs) were prepared by electrospinning with dispersing different amounts of lignin in the polyacrylonitrile (PAN) solutions. Abstract : In this work, lignin/polyacrylonitrile composite fiber-based nonwoven membranes (L–PANs) were prepared by electrospinning with dispersing different amounts of lignin in the polyacrylonitrile (PAN) solutions. The porosity of the L–PANs could reach 74%, which was significantly higher than that of the commercialized PP separator (42%). After exposure at 150 °C for 15 min, the L–PANs showed no apparent dimensional change and no wrinkles, however, the commercialized PP separator shrank by 32%. At the same time, a Li/LiFePO4 battery using L–PANs as a separator delivered superior discharge C-rate capability and cycling performance compared to those using the commercialized PP separator at room temperature. More specifically, the discharge capacity of the cell containing L–PAN (3 : 7 by weight) could retain 148.9 mA h g −1 after 50 cycles at 0.2C and the discharge capacity retention was 95%.